The Language of Heroism: Linguistic and Artistic Dimensions in Homer’s Iliad and Odyssey - Zholaman Taubaevish Koblanov; Umida Khudaybergenova; Roza Kenzhebayeva; Pirniyazova Sholpan Oteniyazovna; Turymbetova Zamira Baymagambetovna; Ziyada Kozhikbaeva (Jurnal Arbitrer, 2025)
This study examines how the distinct linguistic characteristics and narrative structures of Homer’s Iliad and Odyssey contribute to their contrasting portrayals of heroism, with a particular focus on the ethical dimensions of their protagonists. Employing a qualitative descriptive approach, the research utilizes content analysis guided by Peirce’s semiotic theory to decode the layers of meaning embedded in the epics. Primary data consists of Homer’s Iliad and Odyssey in their original Ancient Greek and English translations, supplemented by scholarly commentaries. Specific episodes featuring Achilles and Odysseus were selected and analyzed for key linguistic elements, including diction, epithets, metaphors, and dialogue. The analysis reveals that heroism is conveyed through distinct semiotic patterns across six categories: Heroic Strength and Physicality, Divine Influence and Fate, The Heroic Journey and Struggle, Heroism and Sacrifice, and Moral and Ethical Dimensions, alongside Family and Loyalty. For instance, Achilles’ heroism is often indexed by “swift-footed” and “great-hearted” epithets, emphasizing physical prowess and emotional depth, while Odysseus’ is marked by “wily” and strategic restraint, highlighting intellectual and moral fortitude. The results underscore that Homeric heroism transcends martial prowess, deeply integrating moral decisions, emotional struggles, and familial loyalty as central to heroic identity. These findings challenge simplistic interpretations of Greek heroism, suggesting it encompasses an internal journey of moral growth, loyalty, and personal sacrifice, rather than solely a quest for glory through battle. The study highlights the crucial role of moral responsibility, emotional resilience, and family unity in shaping heroic actions and identities, providing a more nuanced and relatable perspective on heroism for contemporary readers.